Determination of Dieldrin and Polychlorinated Biphenyls in Seawater by Solid Phase Extraction and Capillary Gas Chromatography - LIU Jing; WANG Li; ZENG Xing-yu; ZHANG Yan-ping; WANG Xu-liang (Yankuang ceshi, 2014)
Dieldrin and polychlorinated biphenyls (PCBs) are toxic, organic pollutants that break down extremely slowly in the marine environment. Therefore, it is of valuable significance to establish a rapid, sensitive and accurate detection method for dieldrin and PCBs in seawater. A method has been developed for determining dieldrin and seven PCBs in seawater by Cleanert PS solid-phase extraction and capillary Gas Chromatography with an Electron Capture Detector (GC-μECD). Determination parameters, such as extracting flow rate, eluent, seawater salinity and pH and their effects for extraction efficiency are discussed. By the new method, dieldrin and seven PCBs were extracted from seawater under a flow rate of 5.0 mL/min, eluted by 5.0 mL acetone. The eluate was evaporated, and the solvent was set to 1.0 mL with hexane. The target compounds were determined by GC-μECD. The average recoveries of the method ranged from 82.1% to 123.9% with relative standard deviation (RSD) of 0.9%-4.4%. This method has a better precision compared with the RSD index (1.7%-7.7%) in the specification for marine monitoring (GB 17378.4—2007). The detection limit of dieldrin (0.0088 μg/L) is below the documentary detection limit (0.05 μg/L). Meanwhile, the detection limits of 7 kinds of PCBs range from 0.0012 to 0.0067 μg/L which are below their documentary detection limits (0.147-0.289 μg/L). The established method was qualified for rapid determination of dieldrin and PCBs in seawater samples with a good practical value.